2023
DOI: 10.2215/cjn.0000000000000365
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Activin A, Kidney Fibrosis, and Adverse Events

Ming-Tsun Tsai,
Shuo-Ming Ou,
Kuo-Hua Lee
et al.

Abstract: Background Identification of reliable biomarkers to assess kidney fibrosis severity is necessary for patients with CKD. Activin A, a member of the TGF-β superfamily, has been suggested as a biomarker for kidney fibrosis. However, its precise utility in this regard remains to be established. Methods We investigated the correlation between plasma activin A levels, kidney fibrosis severity, and the incidence of major adverse kidney events in patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, we could not establish a significant association between serum activin levels and graft rejection. This lack suggests that the main mechanism by which activin adversely affects kidney allografts might be profibrotic effects [15, 33, 34]. However, we cannot exclude the possibility of an association between local activin A levels in grafts and rejection, as a previous study reported that activin A was upregulated mainly in the allograft and there was no change in serum activin levels after transplantation and ischemia-reperfusion injury [18].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, we could not establish a significant association between serum activin levels and graft rejection. This lack suggests that the main mechanism by which activin adversely affects kidney allografts might be profibrotic effects [15, 33, 34]. However, we cannot exclude the possibility of an association between local activin A levels in grafts and rejection, as a previous study reported that activin A was upregulated mainly in the allograft and there was no change in serum activin levels after transplantation and ischemia-reperfusion injury [18].…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, many studies have suggested that activin A may act as a pathogenetic factor [31]. Activin A is a potent TGF-βmediated profibrotic substance, is expressed dominantly in myofibroblasts, and has attracted attention as a pathogenetic factor and a therapeutic target in CKD [15,[32][33][34]. Activin has also been linked to immunity and inflammation [35].…”
Section: Discussionmentioning
confidence: 99%
“…Its primary goal is to study kidney transcriptomic profiles and discover new circulating biomarkers for CKD. Tissue specimens were processed per standard procedures and interpreted by an experienced nephropathologist [ 26 , 27 ]. Blood and urine samples were collected on the biopsy day.…”
Section: Methodsmentioning
confidence: 99%